The Application of Dynamic Simulation for Determining Competitive Sales Strategies of Cassava Chips Using iThink - Falleryan, Muhammad; Juanito, Axel; Nurcahya, Dimas; Tosida, Eneng Tita; Subandi, Kotim; Sugara, Victor Ilyas (iora, 2025)
This study aims to determine sales strategies for cassava chips through a dynamic simulation approach using iThink software. The simulation is used to model the factors influencing sales performance, such as fluctuations in raw material prices, operational costs, and market demand patterns. By employing a CLD (Causal Loop Diagram) model and dynamic simulation, this research evaluates various strategies, including product diversification, digital promotion, and distribution efficiency. The simulation results indicate that implementing strategies such as flavor variant diversification and increased promotion through social media can significantly improve sales and profits. Validation was carried out through sensitivity testing on cost and sales parameter changes, demonstrating that dynamic simulation can be an effective tool to support data-driven strategic decision-making